Prealgebra (7th Edition)

Published by Pearson
ISBN 10: 0321955048
ISBN 13: 978-0-32195-504-3

Chapter 3 - Section 3.2 - Integrated Review - Expressions and Equations: 34

Answer

x = 6

Work Step by Step

-6(x - 2) + 10 = -4 - 10 Simplify by distributing -6 into both terms inside the parentheses on the left. -6x - (-12) + 10 = -4 - 10 Simplify. -6x + 12 + 10 = -4 - 10 -6x + 22 = -14 Subtract -22 from both sides to get rid of the 22 on the left and isolate x. -6x = -36 When all terms on both sides of an equation are negative, they can be made positive to make the problem easier to work with, especially when dividing later on. This can be thought of as multiplying both sides by -1, which wouldn't be useful unless all terms were negative. 6x = 36 Divide both sides by 6 to find x. x = 6
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.